Analysis of recombinant DNA clones of the endogenous BALB/c murine leukemia virus WN1802N: variation in long terminal repeat length. - Boone, L R (1983)
We analyzed 15 recombinant DNA clones of the unintegrated closed circular DNA intermediate of the BALB/c endogenous ecotropic murine leukemia virus WN1802N. Thirteen of these clones had an insert which corresponded to the complete murine leukemia virus genome. Of these, six contained a single long terminal repeat (LTR) and seven contained two LTRs. The viral genomes in nine clones had an LTR of 520 base pairs (bp), one had an LTR of 570 bp, three had an LTR of 600 bp, and one had an LTR of 670 bp. Restriction endonuclease analysis demonstrated that the size variability resides in the U3 region. Seven of eight clones which yielded infectious virus by DNA transfection had the 520-bp LTR, and the other had a 600-bp LTR. More detailed examination of plasmid subclones of three isolates with different-sized LTRs revealed that the approximate position which varies in the U3 region corresponds to the 72-bp repeat region of Moloney sarcoma virus. Possible consequences of these variations are discussed.